2013
DOI: 10.1111/jhq.12009
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting and Changing Breast Cancer Screening Recommendations: Survey Study of a National Sample of ob-gyns after the Release of the 2009 USPSTF Guidelines

Abstract: Some ob-gyns made changes to their practices after the release of the USPSTF guidelines. When multiple guidelines exist, as in the case with breast cancer screening, physicians utilize multiple, and at times conflicting, guidelines. More research will be needed to better understand the impact (negative or positive) of multiple guidelines on the quality of healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…12,13,18,20 Another possible explanation could be that the frequency changes to every other year from every year, which could make it harder for older women to remember the last screening date. On the other hand, the fact that more than 2 million women aged 65-74 (40%) did not have a screening mammogram claim in 3 years is a potential concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,18,20 Another possible explanation could be that the frequency changes to every other year from every year, which could make it harder for older women to remember the last screening date. On the other hand, the fact that more than 2 million women aged 65-74 (40%) did not have a screening mammogram claim in 3 years is a potential concern.…”
Section: Discussionmentioning
confidence: 99%
“…Research to date has focused on younger women (age [40][41][42][43][44][45][46][47][48][49], ethnically diverse women, cancer patients, and providers' responses to the change in guidelines; many of the previous studies were based on self-reported survey data looking retrospectively for screening information. [12][13][14][15][16][17][18][19][20] Sharpe et al used Medicare Physician/Supplier Procedure Summary files for [2005][2006][2007][2008][2009][2010] to show that the use of screening mammography decreased in 2010, but they did not examine any differences by age or by regions. 21 The decline in the use of screening mammography found in the Sharpe study could be the result of less frequent screening for younger Medicare beneficiaries or discontinuing screening for women 75 years and older.…”
mentioning
confidence: 99%
“…In this sample, 50% of physicians recommended annual screening to women of ages 40-49 who chose to have such screening, and 97% recommended annual screening to women 50-69 years of age (Anderson, Pearlman, Griffin, & Schulkin, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The timing of our study may also have diminished self-other differences, because the questions regarding patient recommendations focused on the present, whereas personal health practices focused on the past 2-5 years. Given the recent tendency to favor more conservative mammography screening practices, (Anderson et al, 2013) it is possible that physicians' personal preferences at present may be more conservative than their past behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…8 Results indicated that 83.5% of these clinicians were influenced by two or more breast cancer screening guidelines. Although 42% reported making at least one change after the release of the USPSTF recommendations, 73% said that they were more influenced by the ACOG and ACS guidelines.…”
Section: Current Breast Cancer Screening Guidelinesmentioning
confidence: 99%